NATIONALISM APPLYING IN LEARNING CIVIC EDUCATION AS MORAL LEARNING MEDIA IN UNIVERSITY - Rini Setyowati (JETL (Journal of Education, Teaching and Learning), 2016)
This research will review about nationalism in university. The first part of this research will introduce the meaning of nationalism and relation with civic education in university. Nationalism is defined as a love of their country and most citizens feel a sense of nationalism. Civic education in the university is required to strengthen the students in shaping the attitude of nationalism. Students are spearheading the future of a country that they have to love their country because the science which is accepted must be applied in their social life. The main mission of civic education is to help students establish the values of their personality, in order to be able to realize the basic values of Pancasila consistently, also their sense of nationalism in developing science, technology and art with morality. The obstacle of applying nationalism in Civic Education is because of too theoretical and not oriented to the practice of students in community. Inculcation of nationalism should not use indoctrination.We need a civic education in students moral fortify until finally embedded as strong nationalism. This paper using library research. Secondary data was collected by identifying the relevan papers, books, and journal. The data was interpretated and analyzed descriptively. The second part: this research will give solution about method to inculcation of nationalism toward higher educational education. The final part : will give conclusion the best method to inculcation of nationalism in higer educational education and give suggestion to further research about inculcation of nationalism.